QUALITY COSTS AND THEIR IMPACT ON THE COMPETITIVE ADVANTAGE OF INDUSTRIAL COMPANIES: EXPLORATORY STUDY - Zina Adnan Kreem; Aabdulwahab Razzaq Alwan Al-Yasar; Azher Subhi Abdulhussein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of the current research is to determine the importance of financial reporting on the quality cost of industrial companies in Iraq as a way to increase the competitive advantage of these industrial companies, as well as uncover the relationship between the cost of quality and increase the competitive advantage of industrial companies in Iraq. The current study relied on the descriptive analytical approach, through reviewing books, magazines and periodicals, as well as reviewing previous studies related to the topic. The study also relied on all preliminary data through a questionnaire designed to achieve the goal. The study aims to conduct a survey of industrial companies operating in Iraq for the fiscal year 2016. The research reached a number of results, most notably the success of industrial companies in Iraq in improving their competitiveness and their superiority over their competitors through the cost of quality, which requires the need to improve the quality and performance of available resources, Relying on some methods that represent the most important industrial companies can provide the capabilities that allow them to reach to reduce their production costs, and reduce production costs of great importance to improve the ability of industrial companies in Iraq to compete. the cost of quality is one of the most important means and methods to improve the quality of management and raise the level of its performance in the present era, which some call it the era of quality. It is no longer a luxury that industrial companies and industrial companies aspire to or an alternative to take or leave, but it has become an urgent necessity for the contemporary movement of life, which is evidence of The survival of the spirit of survival in the organization or institution and has become one of the important issues, because it is a concrete criterion by which work can be mastered